The Extent to Which the Iraqi Nursing Colleges to the Requirements of Reliability, According to the Indicators of the World Health Organization - AbdulRahman Jassim; Abdul Salam Lafta Saeed (Kufa Journal for Nursing Sciences)
Objective: current research aims to measure the extent to which nursing colleges in Iraqi universities to the requirements of reliability, according to the WHO indicators, and test this model of standards in nursing colleges, and determine the level of availability of accreditation standards for nursing education in the Iraqi nursing colleges. Methodology: The findings are based on a descriptive approach, and its light has been prepared checklist by the researcher based on the World Health Organization model and the model are (6) axes and each axis of two or more as the number of sections (14) portion distributed on (132 ) indicator, and the measure of the extent of the application of the index, which was adopted (9) weights, and was the model examined by eight nursing colleges in Iraqi universities, namely, (Baghdad, Babil, Karbala, Kufa, Muthanna, Maysan, Dhi Qar, Basra), as well as the use of List screening as a tool for gathering information was to use three other instruments, namely, (records, the actual views, and personal interviews), and for the purpose of testing the differences have been relying on the test (Kruskal-Wallis) to test for differences. Results: The researcher found a group of the most important findings was that nursing colleges are working on continuous improvement through attention to global standards in the field of education for nursing Conclusions: The most important conclusions reached by the researcher is the importance of global standards in nursing education being worked on the preparation of nursing staffs with high efficiency. Recommendations recommends research to adopt reliability standards in nursing education, and work on the development (of credit) Council, which is located on the shoulder of credit for all specialties, especially nursing education standards, and the development mode (the nursing profession scientific association) sets standards and identifies programs.